Public Sector Bargaining: From Retrenchment to Consolidation - Rose, Joseph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
There is general agreement that public sector bargaining has evolved through three stages: the expansionary years (mid-1960s to1982), the restraint years (1982-1990) and the retrenchment years (1990s). This paper argues that public sector collective bargaining entered a new stage of development around 1998. The post-retrenchment period or what is referred to as the consolidation stage was marked by economic expansion, the restoration of fiscal stability among the senior levels of government and increases in public employment. Under these conditions, governments and public sector employers sought to consolidate the gains they achieved during the retrenchment years through legislation and hard bargaining. Public sector unions attempted to improve their position by increasing membership and negotiating catch-up wage settlements. Based on a review of selected collective bargaining indicators, employers appear to have consolidated their gains from the retrenchment years.